Between celebration and critique snapshots from 500 years of Philippine Christianity - Francisco, Jose Mario C. Father, S.J (Ateneo de Manila University Press, 2021)
This volume is a very significant and timely contribution to Asian theology. More precisely, it is an excellent introduction to fundamental theology in the Philippines and in Asia. As readers would have surmised, the approach of and issues in fundamental theology in the global south are different from those in the North, which mostly touch upon questions of bridging reason and faith. In contrast, the concern of fundamental theology in the South is how to reconcile culture, history, and agency with the Christian faith. With this volume, Professor Francisco, one of the leading theologians in Asia, will inspire other Asian theologians to do Asian fundamental theology in new and creative ways in consideration of their respective contexts.